PUTUSAN ARBITRASE DALAM PENYELESAIAN SENGKETA PARA PIHAK - Fira Mubayyinah (Al Hikmah: Jurnal Studi Keislaman, 2016)
The court as a means of dispute resolution, most known, but among business will always strive to be avoided by many, due process and the relatively long period of time and protracted due to there are multiple levels in the hierarchy of the courts which have to be passed. In addition it is also because the identity of the parties to the dispute will be known by the public, because the principle of the hearings of the judiciary is, in principle, open to the public. For those who already have a name in the business world, does not want his identity known to the public because the case in court, this was due to worry big name kebonafiditasnya are always protected and preserved will be tarnished, especially among business associates, in addition also for justice that exist in Indonesia today are considered less able to meet the sense of justice in society. Therefore based on the background of the above, to be revealed in this study is whether the Arbitral as an alternative dispute resolution already has a legal binding for the parties to the dispute and shall be final. Arbitral always dependent on technical capabilities Arbiter to give a satisfactory decision and in accordance with the sense of justice of the parties. May not be suitable for the demands made up of various parties. Need to get a court order to do so, when there are parties, especially the losers do not want to implement the Arbitration Award, and (6). Final and binding principles that are attached to the Arbitral not absolutely true, in other words still open a few remedies that can be done to deny an Arbitration Award. Inconsistency of the Arbitral besides a problem, but also make the barriers and obstacles on the level of practice, especially in terms of the execution of an Arbitration Award.